Programming with mobile applications : Android, iOS, and Windows Phone 7 - Duffy, Thomas J. (Course Technology, Cengage Learning, 2013)
Discover how to create effective native apps across platforms and Web apps for today's most popular smartphone platforms with Duffy's PROGRAMMING MOBILE APPLICATIONS: ANDROID(tm), iOS, AND WINDOWS PHONE 7. This unique, hands-on tutorial approach combines clear presentations with numerous screenshots and step-by-step instructions to guide readers in developing applications for Google(tm) Android(tm), Apple iOS, and Windows Phone 7. Readers learn to create identical native and Web apps for each platform, which allows comparing each platform's development processes. The book's complete coverage ranges from platform architecture to native app life cycle management with an emphasis on fundamental programming concepts. This book's unique coverage of multiple platforms not only demonstrates the portability of apps that readers create, but also ensures an solid understanding of programming principles that benefits readers throughout any career.